Impact of ERP investment on company performance Evidence from manufacturing firms in China. - Zhang, Lu; Huang, Jinghua; Xu, Xin.
Information Technology (IT) investments, especially Enterprise Resource Planning (ERP) systems, are critical for the survival and development of companies. Therefore, understanding the impact of ERP investment is of great importance to managers and researchers. As a corporate performance indicator, Tobin's Q has some inherent advantages compared to other accounting indicators, and it can better reflect the contribution of ERP investment to company performance. This study employs multiple regression models to examine the impact of ERP investment on Tobin's Q. The sample consists of 126 manufacturing companies listed on the Shanghai and Shenzhen Stock Exchanges from 1999 to 2007. Empirical results show that in the first three years after ERP implementation, there is no significant change in Tobin's Q; however, in the fourth year, Tobin's Q increases significantly. The results indicate that, as a strategic long-term investment accompanied by large-scale business process reengineering and organizational learning, ERP implementation has time-lagged effects; nonetheless, it eventually produces significant benefits.
Keywords: Biological system modeling; Enterprise Resource Planning (ERP).; Tobin's Q